Experimental evaluation of the efficiency of Epidinocarsis lopezi, a parasitoid introduced into Africa against the cassava mealybug Phenacoccus manihoti - Neuenschwander, Peter; Schulthess, F.; Madojemu, E. (Wiley, 1986)
The capability of Epidinocarsis lopezi (De Santis) (Hymenoptera: Encyrtidae) to control the cassava mealybug (CM) Phenacoccus manihoti Mat.-Ferr. (Homoptera: Pseudococcidae) was investigated in Nigeria using physical and chemical exclusion experiments. In two sleeve cage experiments CM populations, about 2 months after artificial infestation, were 7.0 and 2.3 × lower on artificially infested cassava tips covered with open cages than on tips in closed cages which excluded most parasitoids. On similarly infested but uncovered tips, CM populations were 24.3 and 37.5 × lower, and parasitisation rates were higher. In an artificially infested field which was treated weekly with carbaryl, parasitisation rates were below 10% and CM populations exceeded 200 per tip. In the chemically untreated plot, parasitisation rates were up to 25% and CM densities were mostly below 10 per tip. This study demonstrates the efficiency of E. lopezi in controlling its host under the experimental conditions.